Persepsi Pengunjung terhadap Gelar Melayu Serumpun sebagai Daya Tarik Wisata Budaya di Kota Medan - Prima Yudhistira; Aditiya Pratama Daryana; Vina Gabriella Saragih (Journal of Event, Travel and Tour Management, 2026)
This study aims to explore visitors' perceptions of Gelar Melayu Serumpun as a cultural tourism attraction in Medan. Gelar Melayu Serumpun is a cultural event that showcases various elements of Malay arts, cuisine, and crafts to introduce and preserve Malay culture in North Sumatra. Using a qualitative approach with in-depth interviews and participatory observation, the research analyzes visitors’ experiences and perceptions of the event. A total of 15-20 visitors from diverse backgrounds were selected as research subjects. The results show that the majority of visitors highly appreciate the cultural diversity presented, particularly in terms of Malay cuisine and craft exhibitions, which reflect the heritage of Malay culture. The event was considered successful in providing visitors with a deep understanding of Malay values and history. However, there are areas that need improvement, such as broader promotion outside Medan, which visitors believe would attract more international tourists. Additionally, visitors expressed a desire for more direct interaction with the cultural community, such as workshops or learning sessions on traditional craft-making and cuisine. Based on these findings, it is recommended that the event organizers enhance international promotion and improve facilities such as parking areas and seating. This study provides valuable insights for the development of cultural tourism in Medan and offers recommendations to enhance the quality of existing cultural events, while strengthening Medan's appeal as a competitive cultural tourism destination. Keywords: Gelar Melayu Serumpun; cultural tourism; visitors’ perceptions; traditional arts; Malay cuisine